ULTRASTRUCTURAL STUDY OF GUM MUCOSA IN GENERALIZED MILD DEGREE PERIODONTITIS - Buchkovska, A.Yu.; Nakonechna, O.V.; Petryshyn, O.A.; Strus, Kh.I. (World of Medicine and Biology, 2018)
Currently, periodontal disease is a complex problem that has not only a medical but also a social component. This is due, primarily, to a significant prevalence and intensity of periodontal tissues lesions. In recent years there are new data on the systemic effects of periodontal infection and new methods and approaches to their treatment. The modern principles of the periodontal diseases local therapy are to influence the main pathogenesis of the disease. Despite the achievement of pathogenetically grounded methods, the treatment of patients with periodontitis, the need to search for new effective ways of providing dental care to such patients remains. In therapeutic treatment, the medicinal effect on the pathological lesions is very important for the purpose of the inflammatory process pharmacological correction. Thiotriazolini (5-methyl-1,2,4-triazolin-5-thioacetate) is an active drug that has anti-inflammatory, antioxidant, membrane-stabilizing and immunomodulatory properties. Pharmacotherapeutic action of thiotriazolini is due to membrane stabilizing properties, inhibition of lipid peroxidation processes and activation of antioxidant system enzymes in damaged tissues of the skin and mucous membranes, which leads to a reduction of the traumatic inflammation stage, an increase in the intensity and velocity of the reparative processes, and shortening of treatment. The purpose of the work was to use the method of electron microscopy to study the biopsy of the gum mucosa with generalized periodontitis of the mild degree before treatment and after an anti-inflammatory therapy with 2% ointment of thiotriazolin. Electron microscopic examination of gum mucosa was carried out in 33 patients with periodontitis of mild severity before and after anti-inflammatory therapy. The material for electron microscopic examination (interdental gingival papilla in the area of the anterior lower first incisor) was taken by a surgical scalpel. Ultra-thin sections were made using UMPT-3M ultramicrotome, mounted on supporting nets, and contrasted in 2% uranyl acetate solution. The electron microscopic studies of the gum mucosa have shown that during generalized periodontitis there is a disorganization of all epithelium layers and its own mucous membrane plate, which manifests itself by the expansion of intercellular spaces and by the destruction of desmosomal contacts, loosening of the fibrous structures of the own plate, thinness of the basement membrane, desquamation of microvilli, destruction of the blood vessels endothelial cells organelles of the microcirculatory bed. Thus, in the epithelial plate, between the surface epithelial cells there are destroyed contacts, and there are large intercellular cracks in their place filled with coagulates and precipitates of proteins, bacterial bodies in the form of colonies, hemolysed erythrocytes, platelets and other cellular elements at the stage of decay. Using the method of electron microscopy, the study of gum mucosa in 33 patients with the light severity periodontitis before and after anti-inflammatory therapy was performed. It has been shown that destructive epithelial processes, lamina propria and components of the microcirculatory vessels are observed in the gum. After treatment, it was found that application of thiotriazolin 2% ointment during two weeks stimulate regenerative processes and enhance the protein synthethis, which are manifested by the renovation of the stratum spinosum and stratum basale of the epithelium. Thiotriazolin also stimulates the formation of the new blood capillaries in gums, which is essential for the renovation of blood circulation, the improvement periodontal tissues trophyc and components of the microcirculatory vessels. The use of thiotriazolin in the complex therapy of periodontal diseases reduces the number of treatment sessions by 25% and provides a remote stabilization of the process in 76% patients.